2010
DOI: 10.3747/co.v17i4.567
|View full text |Cite
|
Sign up to set email alerts
|

Has the Practice of Radiation Oncology for Locally Advanced and Metastatic Non-Small-Cell Lung Cancer Changed in Canada?

Abstract: BackgroundAccurate prediction of outcome in advanced nonsmall-cell lung cancer (nsclc) remains challenging. Even within the same stage and treatment group, survival and response to treatment vary. We set out to determine the predictive value of inflammatory markers C-reactive protein (crp) and white blood cells (wbcs) in patients with advanced nsclc. Patients and MethodsPatients were assigned a prognostic index (pi):• 0 for crp 10 mg/L or less and wbcs 11×10 9 /L or less,• 1 if one of the two markers was eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 43 publications
(49 reference statements)
2
89
1
Order By: Relevance
“…Cedrés et al found a direct association between a high neutrophil to lymphocyte ratio NLR value as marker of systemic inflammation and poor prognosis in NSCLC patients, and this was similarly observed by Botta et al in NSCLC patients treated with bevacizumab (38,39). Kasymjanova et al combined CRP and white blood cells (WBCs) in prognostic index and found that it can be a prediction tool for treatment and survival in metastatic NSCLC (40).…”
Section: Discussionmentioning
confidence: 97%
“…Cedrés et al found a direct association between a high neutrophil to lymphocyte ratio NLR value as marker of systemic inflammation and poor prognosis in NSCLC patients, and this was similarly observed by Botta et al in NSCLC patients treated with bevacizumab (38,39). Kasymjanova et al combined CRP and white blood cells (WBCs) in prognostic index and found that it can be a prediction tool for treatment and survival in metastatic NSCLC (40).…”
Section: Discussionmentioning
confidence: 97%
“…The authors suggested that albumin and LDH levels might be used in the risk scoring in further studies. Further studies demonstrated that serum albumin level was a critical prognostic factor in the lung cancer (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014). In these studies, prognostic risk models were created using a number of clinical and laboratory variables and low serum albumin level was found to be one of the poor prognostic factors in the majority of the scoring systems.…”
Section: 5971 Serum Albumin As a Prognostic Factor With Stage Iiib Nmentioning
confidence: 99%
“…With the introduction of recent findings, the Glasgow Prognostic Score (GPS) and the Advanced Lung Cancer Inflammation Index (ALI) on the basis of serum albumin and CRP level have been developed. In addition, further scoring systems such as modified-GPS, Prognostic Index (PI), Adverse Prognostic Factors (APF), and the Montreal Prognostic Score (MPS) based on the performance status, CRP, tumor markers such as carbohydrate antigen (CA)-125, and inflammatory markers such as leukocycte and neutrophil/lymphocyte ratio have been developed (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014). In the majority of these studies, many patients had a metastatic disease (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014).…”
Section: 5971 Serum Albumin As a Prognostic Factor With Stage Iiib Nmentioning
confidence: 99%
“…There were also many studies reporting that haematological markers of systemic inflammatory response such as white blood cell count or its components (neutrophil, lymphocyte, neutrophil-lymphocyte ratio (NLR)), platelet, and platelet-lymphocyte ratio (PLR) are also prognostic indicators for cancer clinical outcomes (Yamanaka et al, 2007;Cho et al, 2009;Kishi et al, 2009;Sarraf et al, 2009;Kwon et al, 2012;Dalpiaz et al, 2013;Fox et al, 2013). In addition, other inflammatory factor combinations such as Prognostic Index (PI) and Prognostic Nutritional Index (PNI) have also been linked with prognosis of malignancies (Kasymjanova et al, 2010;Nozoe et al, 2010;Kanda et al, 2011). However, the value of these markers as independent prognostic factors and the extent these markers improve prognostic classification for patients with inoperable advanced or metastatic GC receiving first-line chemotherapy remains uncertain.…”
Section: Introductionmentioning
confidence: 99%